2019
DOI: 10.1097/cji.0000000000000305
|View full text |Cite
|
Sign up to set email alerts
|

Patched 1-interacting Peptide Represses Fibrosis in Pancreatic Cancer to Augment the Effectiveness of Immunotherapy

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is resistant to immunotherapy. As a factor of resistance, the dense fibrosis of this cancer acts as a barrier to inhibit immune cell infiltration into a tumor. We examined the influence of a Hedgehog signal inhibitor, Patched 1-interacting peptide, on fibrosis, infiltration of immune cells, and immunotherapeutic effects on PDAC. We found that this peptide inhibited proliferation and migration of cancer-associated fibroblasts and cancer cells. Furthermore, this peptide re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Accumulating lines of evidence reveal that hypoxia interacts directly or indirectly with the immune status in the PDAC microenvironment (16,17), yet the mechanism has been under-investigated. Based on the fact that T-cell infiltration (18), DC function (19), etc. are impaired under hypoxia, Yamasaki et al suggest in their review that immunotherapy can only be successful if these hypoxia-immune interaction issues are addressed properly (2).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating lines of evidence reveal that hypoxia interacts directly or indirectly with the immune status in the PDAC microenvironment (16,17), yet the mechanism has been under-investigated. Based on the fact that T-cell infiltration (18), DC function (19), etc. are impaired under hypoxia, Yamasaki et al suggest in their review that immunotherapy can only be successful if these hypoxia-immune interaction issues are addressed properly (2).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the TME has also attracted increased attention (58). We previously reported that inhibition of the Hh signaling pathway suppressed pancreatic cancer fibrosis and promoted intratumoral lymphocyte infiltration in pancreatic cancer (55). As our results indicated that GLI2 may promote tumor fibrosis, we analyzed the association between GLI2 expression and TILs in GBC specimens and found an inverse correlation between GLI2 expression in tumor cells and TIL counts.…”
Section: Discussionmentioning
confidence: 68%
“…This result indicated that GLI2 may be involved in tissue fibrosis in GBC. In our past study of pancreatic cancer, we used pancreatic cancer cells and pancreatic tissue-derived cancer-associated fibroblasts (CAFs) to generate tumors in a xenograft model (55), whereas the reproduction of human pancreatic cancer tissue was not perfect because inducing fibrosis resembling the actual cancer tissue was incomplete. In addition, CAFs derived from GBC tissues has not been established.…”
Section: Discussionmentioning
confidence: 99%
“…PTPs regulate tyrosine phosphorylation in concert with PTK [27] . Low expression of PTPN3, like PTK, may lead to reduction of fibrosis because of the interaction between PTK and PTP, which makes it easier for tumor-infiltrating lymphocytes to infiltrate and increase in tissues [28] . Various factors have been reported to be involved in fibrosis.…”
Section: Discussionmentioning
confidence: 99%